Risk analysis in the production of wine - Zalazar García, Daniela Inés Yanina (2015)
The wine industry is one of the most important in Cuyo. Considering the entire wine sector, it can bementioned that there are associated risks with growing vine, secondly, the associated risks with theprocess of winemaking. This agro-industrial activity are marked by high transience of workers. Atharvest time, the largest number of workers is concentrated, since the contracting meets the needs ofgrowing grapes and special specified conditions for wine making. In addition, there are manyproduction processes, depending on the oenological practices that are carried out at each of thewineries. On the other hand, currently all companies must implement obligatory prevention systemsthat are able to ensure the safety and health of workers as established in Argentine National Securityand Health at Work Law, Number 19587. Industrial accidents are a major physical, psychological andsocial. Also occupational claims ratio is a social prejudice in the worker´s environment, and in turn,economic decline, since in most cases involves the absence or incapacity to perform productiveactivity. Therefore, in this paper, despite the multiple processes of winemaking, unacceptable risksidentification is performed, considering all the possibilities of winemaking. The identification andassessment of risks are fundamental to establish the necessary preventive measures in order tominimize the threat, which generate in the physical, mental and social integrity of the worker. Then,each risk was analyzed and evaluated. Mitigation measures implementation are proposed for identifiedrisks in each stage of this industrial activity. In practice, these measures reduce the frequency and / orseverity of a hazardous event. Subsequently different prevention measures, such as process controland organizational measures are proposed